2021
DOI: 10.1002/hbm.25444
|View full text |Cite
|
Sign up to set email alerts
|

Distinct effects of the basal ganglia and cerebellum on the thalamocortical pathway in idiopathic generalized epilepsy

Abstract: The aberrant thalamocortical pathways of epilepsy have been detected recently, while its underlying effects on epilepsy are still not well understood. Exploring pathoglytic changes in two important thalamocortical pathways, that is, the basal ganglia (BG)-thalamocortical and the cerebellum-thalamocortical pathways, in people with idiopathic generalized epilepsy (IGE), could deepen our understanding on the pathological mechanism of this disease. These two pathways were reconstructed and investigated in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 52 publications
4
15
0
Order By: Relevance
“…As expected, decreased static FC between the thalamus and cortex (frontal and temporal cortex) was observed. This result was consistent with a previous study that showed a decreased correlation in thalamo-temporopolar connection (Bernhardt et al, 2009;Gong et al, 2021). A recent review study showed that there were overlapping findings in patients with GTCS regarding deactivation in the middle/inferior temporal 10.3389/fnins.2022.953356 gyrus (Parsons et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As expected, decreased static FC between the thalamus and cortex (frontal and temporal cortex) was observed. This result was consistent with a previous study that showed a decreased correlation in thalamo-temporopolar connection (Bernhardt et al, 2009;Gong et al, 2021). A recent review study showed that there were overlapping findings in patients with GTCS regarding deactivation in the middle/inferior temporal 10.3389/fnins.2022.953356 gyrus (Parsons et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Graph theory analysis of the structural covariance network of the gray matter found that children with GTCS also showed significant alterations in the nodal betweenness in the right thalamus, bilateral temporal pole, and some regions of DMN (Li et al, 2020b). These previous neuroimaging studies have provided converging evidence for both intrinsic functional connectivity (FC) and structural connectivity abnormalities of the thalamocortical network in patients with GTCS (Kim et al, 2014;Lee et al, 2014;Ji et al, 2015;Li et al, 2016;Wang et al, 2019a;Gong et al, 2021). Focus on the functional and structural changes of thalamo-cortical network would provide additional information to understand the neural mechanism of GTCS.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This previous study has shown that the age of the seizure onset can lead to different perturbations of network modularity and connectivity at the global and local levels in temporal lobe epilepsy, with different implications for regional plasticity and adaptive reorganization. A recent study has found that the FC between the insular and thalamic projections was significantly correlated with the onset of illness in patients with GTCS ( Gong et al, 2021 ). The onset age of illness can affect the brain network organization in patients with GTCS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the deactivation and FC disruption of the DMN in patients with generalized seizures. For example, a previous study in idiopathic generalized epilepsy found enhanced negative FC in the precuneus of the thalamocortical pathway ( Gong et al, 2021 ). The interaction between the thalamocortical pathway and the DMN was disrupted in the generalized epilepsy.…”
Section: Discussionmentioning
confidence: 99%